THE IMPACT OF PRINTING INKS ON THE SAFETY OF PACKAGING FOR FLOUR-BASED CONFECTIONERY PRODUCTS - PELYK, LESYA; REPETA, VIACHESLAV (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article addresses the problem of the impact of printing inks on the safety of paper and cardboard packaging for flour-based confectionery products. The potential migration of low-molecular-weight components of inks (coalescents, plasticizers, mineral oils, etc.) into food products during the storage and use of packaging was investigated. International and national regulatory approaches to controlling the composition of packaging materials and printing inks (EU regulations, EuPIA recommendations, Nestlé practices) were analyzed. Examples of diffusion time calculations for various substances are presented, depending on their molecular weight and the structure of the packaging material. The potential risks of using water-based flexographic inks and oil-based offset inks are characterized, including the occurrence of residual odor, delamination of the ink layer, and migration of chemical compounds into the product. Characteristics of plasticizers and coalescents most commonly used in the production of printing inks are provided, with emphasis on their volatility and migration potential. A model calculation of the influence of cardboard thickness and the molecular weight of plasticizers and coalescents on their diffusion ability was conducted. It was shown, in particular, that the diffusion time of polyethylene glycol PEG-200 is on average 6.6 times longer than that of butyl glycol, while an increase in cardboard barrier thickness additionally prolongs the penetration process. To minimize risks, the use of inks with reduced migration potential, plasticizers with high molecular weight, replacement of mineral oils with vegetable esters, and stricter control in accordance with food safety management requirements (HACCP) are recommended. Within this framework, the need for measures such as predicting the barrier properties of cardboard by accounting for its thickness, monitoring the drying of printed sheets, and adhering to appropriate storage conditions of the packaging has been established.
Keywords: food products; printing ink; packaging safety; confectionery products